Validity Test of an Alternative Method of Quantitative Pain Assessment (MAPKN) in Assessing Intensity of Nociceptive Pain, Mixed Pain, and Neuropathic Pain - Gafur, Rahmi; Susi Aulina; Wuysang, Audry Devisanty; Idris, Irfan; Bahar, Ashari; Hammado, Nurussyariah; Amran, Muhammad Yunus (PT Mattawang Mediatama Solution, 2023)
Pain is a health problem phenomenon that most often brings patients to see a doctor. Pain intensity is the most often domain which assessed in clinical and research settings. Loeser suggests that four elements need to be considered when evaluating patients with pain. Based on the biopsychosocial approach and the concept of pain from Loeser, a pain assessment was made and called